Outcomes of haematology/oncology patients admitted to intensive care unit at The Canberra Hospital. Issue 11 (November 2014) - Parakh, S.; Piggin, A.; Neeman, T.; Mitchell, I.; Crispin, P.; Davis, A.
Abstract: Background: Outcomes for haematology/oncology patients have improved; however, determining their suitability for intensive care unit (ICU) admission remains challenging and controversial. Aim: Examine outcomes of patients admitted to an Australian tertiary hospital ICU and explore potential prognostic factors. Methods: A retrospective review of patients with haematological and solid tumour malignancies non‐electively admitted to The Canberra Hospital (TCH) ICU, between January 2008 and December 2012. Patient demographics, cancer details, reasons for ICU admission and Acute Physiologic and Chronic Health Evaluation (APACHE) II scores were collected, and survival rates calculated and correlated with potential prognostic factors. Results: Of 205 patients, 113 (55%) had haematological malignancies, and 92 (45%) had solid tumours: 58% male and mean age 60.3 years (standard deviation (SD) 13.4). Eighty‐two per cent of solid tumour patients had metastatic disease and 55% received palliative chemotherapy. Primary reasons for ICU admission included sepsis (59%), respiratory distress (37%) and hypotension/shock (18%). Mean APACHE II score was 20.1(SD 0.55); mean length of stay in ICU, 4 days (SD 5.2); ICU survival was 76% with 62% and 41% alive at 30 days and 6 months respectively. Overall 1‐year survival was 36%. High APACHE II scores and ≥2 organs failing were significant risk factors for 30‐day mortality. Conclusion: Short‐term outcomes were similar to contemporary studies from a general tertiary hospital setting and better than historical data. Sixty‐two per cent of patients were alive 30 days post‐ICU admission, with a significant minority alive at 12 months, confirming some patients achieved worthwhile outcomes. Further research is needed to ensure appropriate patient selection and to explore quality of life post ICU.